2014
DOI: 10.1159/000357980
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Naive Myopic Choroidal Neovascularization by Spectral-Domain Optical Coherence Tomography

Abstract: Purpose: To assess the tomographic features of myopic choroidal neovascularization by spectral-domain optical coherence tomography. Methods: We consecutively reviewed the charts of patients with pathologic myopia, recent visual acuity deterioration and active macular neovascularization. Specific tomographic changes were studied in 25 eyes by two authors independently. Results: The mean age of patients eligible for the study was 63.4 (±18.2) years. Main tomographic outcomes were the hyperreflectivity of the les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Similar to the nonmyopic population, the findings in myopic eyes also vary widely: from 23% in Chinese 9 to 11%–40% in Caucasians. 10 , 11 The relationship between ERM and CNV has not been widely investigated, but many authors found lower rates of posterior vitreous detachment in eyes with exudative AMD than in eyes with dry AMD or no disease. 12 14 Since statistically relevant association was also observed between CNV and VMA (located just anterior to the CNV area) in 19%–28% of patients with exudative AMD, 15 , 16 it has been suggested that persistent attachment of the posterior vitreous cortex to the macula may be a risk factor for the development of CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the nonmyopic population, the findings in myopic eyes also vary widely: from 23% in Chinese 9 to 11%–40% in Caucasians. 10 , 11 The relationship between ERM and CNV has not been widely investigated, but many authors found lower rates of posterior vitreous detachment in eyes with exudative AMD than in eyes with dry AMD or no disease. 12 14 Since statistically relevant association was also observed between CNV and VMA (located just anterior to the CNV area) in 19%–28% of patients with exudative AMD, 15 , 16 it has been suggested that persistent attachment of the posterior vitreous cortex to the macula may be a risk factor for the development of CNV.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative parameters included the choroidal thickness [12] (CT) beneath the CNV, the disrupted ellipsoid zone length, [13] the height of the entire lesion defined as the distance between the Bruch membrane and the innermost layer of the disrupted retina, the diameter and height of the CNV, [14] and the thickness of the central macular retinal thickness (CMT) [15]. Qualitative indicators including the CNV location [16] (if the CNV was positioned 1-199 lm from the centre of the area of foveal (as shown by OCT), it was considered foveal-juxtafoveal; if the CNV was positioned at 200 lm or further it was considered extrafoveal), the presence of intraretinal cystic lesions, [17] the presence of sub-retinal fluids (SRF), [17] the presence of subretinal hyperreflective exudation (SHE), [17] the fuzziness of the border of the hyper-reflective CNV lesion, [16] the presence of hyperreflective dots and a shadowing effect towards the choroid, [18] the presence of a "pitchfork sign", and the presence of focal choroidal excavation [19] (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…This could explain why we did not investigate the different SD-OCT features of the neuroretinal layers associated with myopic CNV, which were instead reported in the authors' paper [1] . On the other hand, we wonder whether these features (i.e.…”
mentioning
confidence: 88%